Experimental Study of the Effect of Continuous Surfactant Injection Alternating Cyclic Huff & Puff Stimulation on Oil Efficiency Recovery in A 3D Reservoir Physical Model - David Maurich (Institut Teknologi Sains Bandung, 2019)
Surfactant can displace oil which trapped by capillary effect, make it easier to be produced and finally improve oil recovery factor. However, the effectiveness of surfactant injection depends on many parameters such as surfactant-reservoir fluids properties and interaction, reservoir characteristics and its interaction with surfactant and also surfactant injection scenario or operational methods. This paper discusses about the effect of continuous surfactant injection alternating huff & puff stimulation on oil recovery factor from a quadrant of five-spot pattern in a 3D physical model made from a mixture of sands, cement and water with dimension of 15 cm x 15 cm x 2.5 cm to serve as the surrogate for oil reservoir in laboratory. In order to simulate the oil recovery from a secondary waterflooding process, 0.17 PV of formation water was injected into 3D reservoir physical model. This process could recover about 25.5% OOIP from the physical model, however the injection then shortly terminated due to a drastically increase of watercut. Residual oil then be recovered by a sequence of continuous surfactant injection alternating huff and puff stimulation method. The recovery factor by continuous surfactant injection combine with chase water drive gave a 5.5 % OOIP additional recovery and another 6.8 % OOIP after 24 hours surfactant huff & puff stimulation in the first sequence. After conducting 3 series of a combination of continuous surfactant injection alternating huff & puff stimulation, the total oil recovery from overall processes was about 51.7% OOIP. We presume that the lack of mobility control on macroscopic sweep efficiency in a 3D reservoir physical model is the rationale behind this moderate oil recovery which only produced by surfactant microscopic displacement efficiency. Nevertheless, the research shows that the combination of continuous surfactant injection alternating huff & puff stimulation obviously improve the recovery factor to some extent.